2019
DOI: 10.3390/soc9010012
|View full text |Cite
|
Sign up to set email alerts
|

Text–Image Relationships in Tweets: Shaping the Meanings of an Epidemic

Abstract: 1. Background: While many studies analyze the functions that images can fulfill during humanitarian crises or catastrophes, an understanding of how meaning is constructed in text-image relationships is lacking. This article explores how discourses are produced using different types of text-image interactions. It presents a case study focusing on a humanitarian crisis, more specifically the sexual transmission of Ebola. 2. Methods: Data were processed both quantitatively and qualitatively through a keyword-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…Some of these visual images induce the intergenerational desire and the need to transform body images from an older to a newer one. This finding is consistent with that of Morin et al (2019), who in a study on 'text-image relationships in tweets: shaping the meanings of an epidemic' argued that the research proposes a four-category classification of text-image relationships.…”
Section: Body Image Socialization and Culturesupporting
confidence: 89%
See 2 more Smart Citations
“…Some of these visual images induce the intergenerational desire and the need to transform body images from an older to a newer one. This finding is consistent with that of Morin et al (2019), who in a study on 'text-image relationships in tweets: shaping the meanings of an epidemic' argued that the research proposes a four-category classification of text-image relationships.…”
Section: Body Image Socialization and Culturesupporting
confidence: 89%
“…Many studies concentrate on social functions involving images such as the rise of 'citizen journalists' (Murthy, 2011), the documentation and management of life's catastrophes (Terpstra et al, 2012) and political crisis (Vis et al, 2013), or they limit themselves to analyzing how images contribute to the discursive construction of an event (Kharoub & Bas, 2015;Seltzer et al, 2015). Morin et al (2019) note that the relationship between text and image is admittedly a very specific topic of research, however, it is essential to understand meanings on social media. Detaching texts from images or postulating the superiority of texts over images runs the risk of skewing research results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The visual Tweets were not very productive messages in a crisis probably because they cannot adequately satisfy the elevated information needs in the crisis. Moreover, in such a situation, text Tweets are often the primary discourse and visuals are just complementary to text, a way to add something to what is in the text (Morin et al, 2019). Further, our analysis confirmed that in a public health crisis, connecting with hyperlinks to a richer source of information could be another very productive way to drive citizens' participatory engagement provided the associated website was a credible source of information.…”
Section: Discussionsupporting
confidence: 61%
“…encourage them to react, comment, and share), community managers often add a text above the photo. As stated by Morin et al (2019) , “Images are a powerful vector of signification that social media users resort to more and more” (p. 1). The main characteristic of visual material is that it generates emotions: “Images are considered capable of drawing people along an emotional pathway, while textual or verbal material encourages them to follow a more rational, logical and linear thought process” ( Joffe, 2007 : 102, our translation).…”
mentioning
confidence: 99%